Pengembangan E-LKPD Berbasis Problem Based Learning Menggunakan Aplikasi Book Creator di Kelas III Sekolah Dasar - Latifah Hanum; Risda Amini (Elementary Teacher Education Program, Majalengka University, 2023)
interest and attention in learning. This purpose of this research is to determine the validity and practicality of develop E-LKPD using the Book Creator application based on Problem Based Learning in integrated thematic learning in class III elementary schools. This research is Research and Development (R&D) with ADDIE model (analysis, design, development, implementation, evaluation). The results of this research obtained from the results of validity and practicality tests. Validity test results obtained from material, media and language expert validators. The validity test results obtained results in the very valid category with a validity percentage of 96,15% from material experts, 98,48% from media experts, and 96,66% from language experts. Practicality test results obtained from teacher and student response questionnaires. The results of the practicality test at the trial school obtained results in the very practical category with a practicality percentage of 90,63% from the teacher response questionnaire and 90,16% from the student response questionnaire. The implementation school obtained results in the very practical category with a practicality percentage of 93,75% from the teacher response questionnaire and 92,97% from the student response questionnaire.